Coronavirus disease 2019 (COVID-19) in a kidney transplant recipient; case report - Martin Thomas Kurian; Syed Arman Rabbani; Ajith Cherian Thomas; Nadeem Javed (Society of Diabetic Nephropathy Prevention, 2022)
Patients with kidney transplants are at greater risk of contracting COVID-19 because of long-term immunosuppression and may end up with severe disease with adverse outcome. The experiences of COVID-19 management in kidney transplant recipients are limited. This is a case of COVID-19 in a 45-year-old patient with a second renal transplant on triple immunosuppressive therapy who was successfully treated for COVID-19, septic shock, acute kidney injury and was discharged with a stable graft function. The patient presented with mild COVID-19 symptoms but later went into septic shock followed by acute kidney injury due to a secondary bacterial infection. The patient was successfully managed using antivirals, corticosteroids, reducing the dose of immunosuppressants initially, then discontinuing all the immunosuppressants in view of septic shock and finally reinstating the immunosuppression gradually on clinical improvement. This case report may serve as a reference for treating immunocompromised kidney transplant recipients having COVID-19. However, more data and experiences are needed for optimization of treatment of kidney transplant recipients with COVID-19.